Amyloid-like Self-Assembly of a Hydrophobic Cell-Penetrating Peptide and Its Use as a Carrier for Nucleic Acids - de Mello, Lucas R; Porosk, Ly; Lourenço, Thiago C; Garcia, Bianca B. M; Costa, Carlos A. R; Han, Sang W; de Souza, Juliana S; Langel, Ülo; da Silva, Emerson R (ACS applied bio materials, 2021)
Cell-penetrating peptides (CPPs) are a topical subject potentially exploitable for creating nanotherapeutics for the delivery of bioactive loads. These compounds are often classified into three major categories according to their physicochemical characteristics: cationic, amphiphilic, and hydrophobic. Among them, the group of hydrophobic CPPs has received increasing attention in recent years due to toxicity concerns posed by highly cationic CPPs. The hexapeptide PFVYLI (P, proline; F, phenylalanine; V, valine; Y, tyrosine; L, leucine; and I, isoleucine), a fragment derived from the C-terminal portion of α1-antitrypsin, is a prototypal example of hydrophobic CPP. This sequence shows reduced cytotoxicity and a capacity of nuclear localization, and its small size readily hints at its suitability as a building block to construct nanostructured materials. In this study, we examine the self-assembling properties of PFVYLI and investigate its ability to form noncovalent complexes with nucleic acids. By using a combination of biophysical tools including synchrotron small-angle X-ray scattering and atomic force microscopy-based infrared spectroscopy, we discovered that this CPP self-assembles into discrete nanofibrils with remarkable amyloidogenic features. Over the course of days, these fibrils coalesce into rodlike crystals that easily reach the micrometer range. Despite lacking cationic residues in the composition, PFVYLI forms noncovalent complexes with nucleic acids that retain β-sheet pairing found in amyloid aggregates. In vitro vectorization experiments performed with double-stranded DNA fragments indicate that complexes promote the internalization of nucleic acids, revealing that tropism toward cell membranes is preserved upon complexation. On the other hand, transfection assays with splice-correction oligonucleotides (SCOs) for luciferase expression show limited bioactivity across a narrow concentration window, suggesting that the propensity to form amyloidogenic aggregates may trigger endosomal entrapment. We anticipate that the findings presented here open perspectives for using this archetypical hydrophobic CPP in the fabrication of nanostructured scaffolds, which potentially integrate properties of amyloids and translocation capabilities of CPPs.